Broadening of effective photonic band gaps in biological chiral structures: From intrinsic narrow band gaps to broad band reflection spectra. (29th September 2015) - Vargas, W. E.; Hernández-Jiménez, M.; Libby, E.; Azofeifa, D. E.; Solis, Á.; Barboza-Aguilar, C.
Abstract: Under normal illumination with non-polarized light, reflection spectra of the cuticle of golden-like and red Chrysina aurigans scarabs show a structured broad band of left-handed circularly polarized light. The polarization of the reflected light is attributed to a Bouligand-type left-handed chiral structure found through the scarab's cuticle. By considering these twisted structures as one-dimensional photonic crystals, a novel approach is developed from the dispersion relation of circularly polarized electromagnetic waves traveling through chiral media, to show how the broad band characterizing these spectra arises from an intrinsic narrow photonic band gap whose spectral position moves through visible and near-infrared wavelengths.